THE ROLE OF PRIMARY CARE IN REDUCING HEALTHCARE COSTS A CASE STUDY OF PREVENTIVE INTERVENTIONS AND RESOURCE ALLOCATION (The Research of Medical Science Review, 2024)
This study examines the potential of primary care to minimize costs of care delivery by undertaking preventive health measures and proper utilization of scarce resources. Based on a case study of the primary care system the study focuses on effects of the targeted preventive activities like diabetes and hypertension among the population. Quantitative cost analyses and qualitative stakeholder interviews demonstrate a substantial reduction in costs for individuals, reductions in morbidity/mortality rates, and better management of all resources across the system. These results also emphasize the benefits of shifting healthcare systems from focusing on acute disease care towards preventive health models that have fiscal and societal value through decreased morbidity and enhanced health in the general population. Analysis with international counterparts establishes the sizes of these interventions, and the discussion establishes concerns, including resource shortages and implementation hurdles. Personnel observe that there is a need for change transformation, policy changes, and partnerships in order to address such challenges. The study re-emphasizes the centrality of primary care in the achievement of long-term and efficient solutions to healthcare problems while calling for increased investment in early prevention.